Poetry, History, Memory Wang Jingwei and China in Dark Times - Yang, Zhiyi (University of Michigan Press, 2023)
Wang Jingwei, poet and politician, patriot and traitor, has always been a figure of major academic and popular interest. Until now, his story has never been properly told, let alone critically investigated. The significance of his biography is evident from an ongoing war on cultural memory: modern mainland China prohibits serious academic research on wartime collaboration in general, and on Wang Jingwei in particular. At this critical juncture, when the recollection of World War II is fading from living memory and transforming into historical memory, this knowledge embargo will undoubtedly affect how China remembers its anti-fascist role in WWII. In Poetry, History, Memory: Wang Jingwei and China in Dark Times, Zhiyi Yang brings us a long overdue reexamination of Wang's impact on cultural memory of WWII in China. In this book, Yang brings disparate methodologies into a fruitful dialogue, including sophisticated methods of poetic interpretation. The author argues that Wang's lyric poetry, as the public performance of a private voice, played a central role in constructing his political identity and heavily influenced the public's posthumous memory of him. Drawing on archives (in the PRC, Taiwan, Japan, the USA, France, and Germany), memoires, historical journals, newspapers, interviews, and other scholarly works, this book offers the first biography of Wang that addresses his political, literary, and personal life in a critical light and with sympathetic impartiality.